2006
DOI: 10.1111/j.1439-0418.2005.01030.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nitrogen fertilization of corn on the development, survivorship, fecundity and body weight of Peregrinus maidis (Hom., Delphacidae)

Abstract: Corn plants, Zea mays L. cv. Saccharata ÔGuardianÕ fertilized with low (100 mg N/l), medium (300 mg N/l) and high (500 mg N/l) nitrogen doses at three times per week were used to study the effect of foliar nitrogen on the development, survivorship, reproduction, intrinsic rate of increase and adult body weight of Peregrinus maidis (Ashmead), a serious pest and the vector of maize stripe tenuvirus and maize mosaic rhabdovirus in tropical and subtropical areas. The results showed that the higher nitrogen treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 25 publications
3
33
0
1
Order By: Relevance
“…gossypii adult longevity was positively correlated with nitrogen levels in the leaf tissue. Similar effects on adult longevity have been documented for another phloem-feeding insect, the plant hopper Peregrinus maidis (Ashmead), (Hom., Delphacidae) (Wang et al 2006). However, Moon et al (1995) reported that varying nitrogen levels did not significantly change the duration of either the reproductive period or adult longevity of the Russian wheat aphid Diuraphis noxia (Mordvilko).…”
Section: Discussionmentioning
confidence: 96%
“…gossypii adult longevity was positively correlated with nitrogen levels in the leaf tissue. Similar effects on adult longevity have been documented for another phloem-feeding insect, the plant hopper Peregrinus maidis (Ashmead), (Hom., Delphacidae) (Wang et al 2006). However, Moon et al (1995) reported that varying nitrogen levels did not significantly change the duration of either the reproductive period or adult longevity of the Russian wheat aphid Diuraphis noxia (Mordvilko).…”
Section: Discussionmentioning
confidence: 96%
“…Nevertheless, a review of published papers with the Hach method shows that the researchers who use this technique frequently belong to a few areas, such as food science and nutrition (e.g., Vidrih and Hribar 1999;Adour et al 2002Adour et al , 2004 and agriculture (e.g., Snow et al 2004;Harvatine and Allen 2006;Wang et al 2006). Possibly, high demands for total nitrogen analysis (and/or control of food regarding protein content) in these areas contribute to make the Hach method more popular.…”
Section: Introductionmentioning
confidence: 99%
“…Our results also suggest, however, that invasive species are likely to be dependent on a more specialized diet with a high proportion of protein in order to support high rates of growth [37,38]. This may further explain why invasive species including A. lusitanicus often thrive in cultivated habitats, as these are normally well fertilized with nitrogenous compounds which increases plant protein content [53,54]. This prediction could be explicitly tested by applying the geometric framework to related invasive and non-invasive species and comparing nutrient regulation compromises and capabilities and the subsequent effects of nutritional imbalance on performance.…”
Section: Discussionmentioning
confidence: 64%